2021
DOI: 10.3390/ijerph181910197
|View full text |Cite
|
Sign up to set email alerts
|

Root Canal Morphology and Configuration of the Mandibular Canine: A Systematic Review

Abstract: The aim of this study was to systematically review the root canal morphology and configuration (RCC) of mandibular canines (MaCa). The review was registered in the PROSPERO database (ID-272297) and it was carried out following the PRISMA guidelines. Three electronic databases (MEDLINE via PubMed, Embase, Scopus) were searched. Randomized controlled trials, cross-sectional, cohort, comparative, evaluation and validation studies have been included. The anatomical quality assessment (AQUA) tool was used for a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
(297 reference statements)
0
7
0
Order By: Relevance
“…The current systematic review was constructed and designed according to the Preferred Reporting Items for Systematic Review and Meta-analysis. [68][69][70]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current systematic review was constructed and designed according to the Preferred Reporting Items for Systematic Review and Meta-analysis. [68][69][70]…”
Section: Methodsmentioning
confidence: 99%
“…The value of the involved published original research and case reports studies was evaluated using the recommendations of the Strengthening the Reporting of Observational Studies in Epidemiology. [68][69][70] For the Saudi studies, five studies had good quality, whereas most of the case reports were had low or fair quality. The international studies in both forms as original and/or case reports papers were good quality reports.…”
Section: Study Characteristics and Quality Of The Included Studiesmentioning
confidence: 99%
“…Most permanent mandibular canines (PMCs) have one root and one canal [5][6][7][8][9]. PMCs with two roots and two canals occur at a prevalence of 0.0 to 12.1% worldwide and 0.2 to 2.9% in Saudi Arabia [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Most permanent mandibular canines (PMCs) have one root and one canal [5][6][7][8][9]. PMCs with two roots and two canals occur at a prevalence of 0.0 to 12.1% worldwide and 0.2 to 2.9% in Saudi Arabia [5,6]. Although this root canal morphology is rare, dental clinicians must be aware of variations in the number of roots and canals for proper case management, as unpredicted findings in root canal morphology can have a significant negative impact on endodontic treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The growing evidence demonstrated the incidence of the additional root in different types of teeth. The accessory root revealed approximately 0.8% at the palatal root of permanent maxillary first molars in the Greece-Turkish population [ 20 ], around 8% in permanent mandibular second premolars of the Indian population [ 21 ], up to 12% in permanent mandibular canines of the Iranian population [ 22 ], and almost 16% in permanent mandibular first premolars of the African-American population, respectively [ 23 ]. For PMFM, an earliest systematic review of the scope investigated that the pooled prevalence of three-rooted PMFM revealed 13% with the highest value of 22% in the Chinese population [ 24 ].…”
Section: Introductionmentioning
confidence: 99%